Drinking Together and Drinking Alone: A Social-Contextual Framework for Examining Risk for Alcohol Use Disorder - Creswell, Kasey G. (Current directions in psychological science : a journal of the American Psychological Society, 2021)
The context in which drinking occurs is a critical but relatively understudied factor in alcohol use disorder (AUD) etiology. In this article, I offer a social-contextual framework for examining AUD risk by reviewing studies on the unique antecedents and deleterious consequences of social compared with solitary alcohol use in adolescents and young adults. Specifically, I provide evidence of distinct emotion regulatory functions across settings, in which social drinking is linked to enhancing positive emotions and social experiences, and solitary drinking is linked to coping with negative emotions. I end by considering the conceptual, methodological, and clinical implications of this social-contextual account of AUD risk.